Adapting the Grimms: Going Against Patriarchy in Singh’s Movie Mirror Mirror (Journal of the College of Education for Women, 2022)
Many cinematic adaptations were produced for the Grimms’ “Little Snow-White” (1812) including Mirror Mirror movie (2012), the contemporary version adapted by Taresm Singh. Singh’s version was able to depict the modern reality of women and went against patriarchy by embracing feminist ideologies of the fourth-wave feminism. Therefore, he challenged the ideologies of the mainstream cinema dominated by the patriarchal élite’s capitalist mode of production that still adhere to the stereotyped patriarchal image of women’s ‘victimization,’ ‘objectification’ and ‘marginalization,’ which did not represent women’s modern reality anymore. This paper, however, is a qualitative study aimed to prove that the feminist ideologies could only be retained after a cultural transformation process from the patriarchal élite culture to the popular culture of mass media after the World War II, which noticeably affected women’s image in the cinema. And thus, this paper is an analytical study of Mirror Mirror that used the analytical textual and production approaches to popular culture along with the Marxist and feminist film theories to unfold the feminist ideologies prevailed in the movie. The study has concluded that the cultural transformation from the patriarchy into the popular culture of mass media led to the emergence of counter-cinema or cinefeminism that encouraged the reversing of the traditional gender roles in cinema. It has also shown that class conflict and economic power caused by the cultural transformation helped in redefining women’s role and place in society. Thereby maintaining the feminist ideologies of the fourth-wave’s ‘women’s empowerment’ positively affected women and girls to reflect their modern reality